Immunotherapy is different: Implications for vaccine clinical trial design - Richard Simon (Taylor & Francis Group, 2017)
Cancer Immunotherapetics differ fundamentally from most cancer therapies in that they involve manipulation of the immune system to induce an anti-tumor response. This fundamental difference results in differences in the pre-clinical and clinical development of immunotherapeutics. Even the regulatory culture of developing one drug at a time and demonstrating that it, when added to standard therapy, prolongs patient survival, is often not suitable for the development of effective immunotherapy regimens. In this commentary, we explore some of these differences and describe novel clinical trial designs which may be useful in immunotherapeutics regimen development.